Adaptive Control Design for Arneodo Chaotic System with Uncertain Parameters and Input Saturation. (13th February 2020) - Cheng, Chunhua; Gao, Fengjuan; Xu, Jingshuo; Wang, Yuanxin; Yuan, Tao
Abstract : In this paper, tracking controller and synchronization controller of the Arneodo chaotic system with uncertain parameters and input saturation are considered. An adaptive tracking control law and an adaptive synchronization control law are proposed based on backstepping and Lyapunov stability theory. The adaptive laws of the unknown parameters are derived by using the Lyapunov stability theory. To handle the effect caused by the input saturation, an auxiliary system is used to compensate the tracking error and synchronization error. The proposed adaptive tracking control and synchronization schemes ensure the effects of tracking and synchronization. Several examples have been detailed to illuminate the design procedure.